In situ synthesis of V2O3@Ni as an efficient hybrid catalyst for the hydrogen evolution reaction in alkaline and neutral media. (19th February 2021) - Hu, Mingwei; Huang, Jin; Zhang, Song; Liu, Zhizhuang; Li, Qizhong; Yang, Meijun; Li, Haiwen; Goto, Takashi; Tu, Rong
Abstract: The exploration of cheap and efficient electrodes for hydrogen evolution reactions (HER) is extremely challenging. Herein, we report a newly-designed V2 O3 @Ni hybrid grown in situ on nickel foam as an efficient HER catalyst. The nickel foam not only promoted the electron transfer rate as a supporting substrate, but also worked as the source of Ni to enhance the integration of catalyst components with abundant active sites. Moreover, benefitting from the synergistic effect of the interface between V2 O3 and Ni, which accelerated the entire electrochemical kinetics and facilitated the electron transfer, the in situ V2 O3 @Ni hybrid catalysts afforded a small overpotential of 47 mV and 100 mV at a current density of 10 mA cm −2 in 1.0 M KOH and 1.0 M PBS, respectively, and with excellent long-term stability. In addition, this research provides a new route for the fabrication of noble-metal-free electrocatalysts with excellent HER performance over a broad range of pH values. Highlights: A newly-designed V2 O3 @Ni hybrid were in situ grown on nickel foam. It afforded overpotential of 47 and 100 mV at 10 mA cm −2 in 1.0 M KOH and 1.0 M PBS. The interface between Ni and V2 O3 plays the major role in boosting the HER activity.